SUBJECT-OBJECT INTERACTION RECOGNITION MODEL - SMEULDERS, Arnold Wilhelmus Maria; GAVVES, Efstratios; KILICKAYA, Mert (2022)
A method for processing an image is presented. The method locates a subject and an object of a subject-object interaction in the image. The method determines relative weights of the subject, the object, and a context region for classification. The method further classifies the subject-object interaction based on a classification of a weighted representation of the subject, a weighted representation of the object, and a weighted representation of the context region.